Computer Aided Surgery 7th Asian Conference on Computer Aided Surgery, Bangkok, Thailand, August 2011, Proceedings - Dohi, Takeyoshi; Liao, Hongen; SpringerLink (Online service) (Tokyo : Springer Japan, 2012)
The aim of computer-aided surgery (CAS) is to advance the utilization of computers in the development of new technologies for medical services. The Asian Conference on Computer Aided Surgery (ACCAS) series provides a forum for academic researchers, clinical scientists, surgeons, and industrial partners to exchange new ideas, techniques, and the latest developments in the field. The ACCAS brings together researchers from all fields related to medical activity visualization, simulation and modeling, virtual reality for CAS, image-guided diagnosis and therapies, CAS for minimally invasive intervention, medical robotics and instrumentation, surgical navigation, clinical application of CAS, telemedicine and telesurgery, and CAS education. The ACCAS is also interested in promoting collaboration among people from different disciplines and different countries in Asia and the world. This volume helps to achieve that goal and is a valuable resource for researchers and clinicians in the field.
Keywords: Computer science; Artificial intelligence; Computer vision; Computer aided design; Electronics; Biomedical engineering; Computer Science; Artificial Intelligence (incl. Robotics).; Computer-Aided Engineering (CAD, CAE) and Design; Computer Imaging, Vision, Pattern Recognition and Graphics; Biomedical Engineering; Electronics and Microelectronics, Instrumentation